Plant-based protein market in Asia - Rajpal, Harsh (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Harsh Rajpal, Code Partners Pte. Ltd., on 30 June 2021 at the Asian Development Bank (ADB) Webinar on Sustainable Protein Case Study: Outputs and Synthesis of Results.